Beef trait genetic parameters based on old and recent data and its implications for genomic predictions in Italian Simmental cattle. (30th July 2020) - Cesarani, Alberto; Hidalgo, Jorge; Garcia, Andre; Degano, Lorenzo; Vicario, Daniele; Masuda, Yutaka; Misztal, Ignacy; Lourenco, Daniela
Abstract: This study aimed to evaluate the changes in variance components over time to identify a subset of data from the Italian Simmental (IS ) population that would yield the most appropriate estimates of genetic parameters and breeding values for beef traits to select young bulls. Data from bulls raised between 1986 and 2017 were used to estimate genetic parameters and breeding values for four beef traits (average daily gain [ADG ], body size [BS ], muscularity [MUS ], and feet and legs [FL ]). The phenotypic mean increased during the years of the study for ADG, but it decreased for BS, MUS, and FL. The complete dataset (ALL ) was divided into four generational subsets (Gen1, Gen2, Gen3, and Gen4 ). Additionally, ALL was divided into two larger subsets: the first one (OLD ) combined data from Gen1 and Gen2 to represent the starting population, and the second one (CUR ) combined data from Gen3 and Gen4 to represent a subpopulation with stronger ties to the current population. Genetic parameters were estimated with a four-trait genomic animal model using a single-step genomic average information restricted maximum likelihood algorithm. Heritability estimates from ALL were 0.26 ± 0.03 for ADG, 0.33 ± 0.04 for BS, 0.55 ± 0.03 for MUS, and 0.23 ± 0.03 for FL. Higher heritability estimates were obtained with OLD and ALL than with CUR. Considerable changes in heritability existed between Gen1 and Gen4 due to fluctuations in both additive genetic and residual variances. Genetic correlations also changed over time, with some values moving from positive to negative or even to zero. Genetic correlations from OLD were stronger than those from CUR. Changes in genetic parameters over time indicated that they should be updated regularly to avoid biases in genomic estimated breeding values (GEBV ) and low selection accuracies. GEBV estimated using CUR variance components were less biased and more consistent than those estimated with OLD and ALL variance components. Validation results indicated that data from recent generations produced genetic parameters that more appropriately represent the structure of the current population, yielding accurate GEBV to select young animals and increasing the likelihood of higher genetic gains.